Food antigen-specific IgE in dogs with suspected food hypersensitivity - Baumann, Sandra A.; Fritz, Cornelius; Mueller, Ralf S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2020)
Objective Knowledge of cross-reactions in food-sensitive dogs will influence the choice of elimination diets and the long-term management of those patients. The objective of this study was to evaluate food allergen-specific IgE tests of suspected allergic dogs for concurrent positive reactions as possible evidence for cross reactions between allergens.Material and methods Results of serum IgE tests from 760 suspected allergic dogs submitted to 2 laboratories were evaluated statistically. After the tested allergens were grouped by their phylogenetic relationship, odds ratios as well as a sensitivity analysis of the odds ratios were performed to evaluate if concurrent positive IgE results to 2 allergens occurred more often than expected.Results Within related allergen pairs 27% (laboratory 1) and 72% (laboratory 2) of the pairs could be considered as associated. For the unrelated allergen pairs only 6.8% and 10.6% of the analyzed pairs were considered associated respectively. Strong correlations were shown in the group of ruminant allergens, especially beef and lamb, and grain allergens. High rates of concurrent reactions were also detected in the poultry group, especially between chicken and duck, as well as between pork and ruminant allergens, and soy and grain allergens.Conclusion As our results showed not only correlations within related but also between non-related allergens, the possible relevance of carbohydrate moieties as well as panallergens for canine hypersensitivities warrants further study. Further investigations are necessary to distinguish co-sensitization from cross-reactions and determine the clinical relevance of food-specific IgE reactivity.Clinical relevance Due to possible cross reactivity related allergens, especially beef and lamb as well as grain allergens, should not be used for an elimination diet to avoid false results.
Keywords: Food allergy; food hypersensitivity; cross-reactions; co-sensibilization; dermatology